COVID-19 olfactory dysfunction, evaluation of onset, and persistence - Abdulhusein Mizhir Almaamuri; Mohammed M Mohammed (Wolters Kluwer Medknow Publications, 2023)
Olfactory dysfunction (OD) is a common feature of COVID-19. The goal of the study was to define the modes of onset of OD in the clinical course of the disease and to follow the cases for 12-18 months in order to estimate the differences in the recovery time from OD over the course of the disease. We managed to follow a total of 325 patients (females: 198, males: 127) in the Babylon governorate in Iraq. All were COVID-19 patients who should have OD during the course of the disease. COVID-19 infection was established in all patients by swab test, i.e. polymerase chain reaction (PCR) and/or chest computed tomography findings of pneumonia compatible with COVID-19. Detailed medical records were obtained directly from the patients or their relatives. The patients were then followed up by telephone and questioned with structured questionnaires concentrating upon general clinical features and the sense of olfaction. Information about the presence of olfactory disorders, their occurrence, and development was recorded. Based on the onset of OD, the patients were categorized into three groups. Olfactory functions were assessed primarily by face-to-face interview and then (if necessary) by a telephone questionnaire assessing self-reported olfactory function and olfactory-related quality of life, which measures the subjective olfactory capability (SOC). In the first 2 weeks, 148 (45.5%) patients reported complete recovery from OD, of which 90 (73.2%) patients joined at the end of the 1st month. OD persistence was observed in 11 (3.3%) patients toward the end of the 1st year, in 5 (1.5%) patients at the end of the 15th month, and only in two (0.6%) patients at the end of the 18th month. We found no significant correlation between the type of onset of OD and the duration and persistence of OD. Most sufferers of COVID-associated OD recover their sense of smell within the 1st month.